2020
DOI: 10.20964/2020.03.39
|View full text |Cite
|
Sign up to set email alerts
|

Failure Behavior and Damage Mechanism of Acrylic Polyurethane Coating in Tropical Marine Atmospheric Environment

Abstract: Acrylic polyurethane coating was exposed to the tropical marine atmospheric environment for 24 months, and the physical, chemical and protective properties of the coating were investigated. The results demonstrated that the appearance, adhesion and protective property of the coating were degraded rapidly in the early exposure stage, and then changed slowly in the late exposure stage. During the filed exposure test, the ultraviolet irradiation was a major contributor to polyurethane chain scission of the coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The thermal degradation of the polyurethane coating can be divided into two main stages, each involving specific reactions during the decomposition process. Hard segment degrading is what is responsible for the initial stage, which includes urethane groups and hydrogen bonding [3,14]. This stage commences at 236°C and concludes at 320°C, with the highest temperature degradation rate of weight loss occurring at 275°C (t max1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal degradation of the polyurethane coating can be divided into two main stages, each involving specific reactions during the decomposition process. Hard segment degrading is what is responsible for the initial stage, which includes urethane groups and hydrogen bonding [3,14]. This stage commences at 236°C and concludes at 320°C, with the highest temperature degradation rate of weight loss occurring at 275°C (t max1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For surface wettability and improving adhesion and bond strength, various surface treatment techniques have been addressed in recent years [6][7][8][9][10][11]. Adhesion properties (cross-cut, pull-off adhesion and peel strength), corrosion resistance, water immersion studies, tribological performance (taber abrasion and pin-on-disc), tensile properties, DSC, FTIR and TGA studies, WCA were investigated and reported by a few authors [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to their barrier effect against corrosive media and their inhibition effect on corrosion reactions, PU coating is also an ideal candidate utilized in mitigating the corrosion of metals [ 5 , 6 ]. However, the factors of light, oxygen, microorganisms, temperature, and moisture can damage the cross-link structures of PU and accelerate the formation of blistering and chalking [ 7 , 8 ]. Among them, the first three factors dominantly contribute to the degradation of PU in natural environments [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%